If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 83 = m + 40 Reorder the terms: 83 = 40 + m Solving 83 = 40 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 83 + -1m = 40 + m + -1m Combine like terms: m + -1m = 0 83 + -1m = 40 + 0 83 + -1m = 40 Add '-83' to each side of the equation. 83 + -83 + -1m = 40 + -83 Combine like terms: 83 + -83 = 0 0 + -1m = 40 + -83 -1m = 40 + -83 Combine like terms: 40 + -83 = -43 -1m = -43 Divide each side by '-1'. m = 43 Simplifying m = 43
| 0.04(y-9)+0.20y=0.16y-0.01(30) | | 4(2z-4)= | | 9(11-k)= | | -81=n-47 | | 7(n+3)-8=6 | | k+(-23)=-51 | | 1/3p-1/6p=-3 | | (4125*3-50)+(512/2-20) | | 18=2-x | | a-42=-54 | | 5c/8-c/3=5c/6-13 | | 7=-11+x | | 39+15a=24 | | a+-10=-19 | | (3654-20/2)-(810*3-500) | | -f/4+7=-6 | | h(a)=3a^2-3 | | 2/3d+1=16-d | | 24=n(-24) | | 6m+11=85 | | 4x^2-4x-80=0 | | 180=x+2x+(x+8) | | 6z+0.20=7z+0.40 | | 50+1.99m=0+3.99m | | (x)7+(-6)=-20 | | 12=15-v | | -40=-46+n | | 5x^2+11=2x^2-25 | | 6+-7(x)=-20 | | 8-x=-28 | | 4x+3(2x+7)=31 | | 5+y=84/9 |